Prevalence and triage of first‐contact complaints on pelvic floor dysfunctions in female patients at a Pelvic Care Centre. Issue 4 (23rd March 2015) - Berghmans, Bary; Nieman, Fred; Leue, C.; Weemhoff, M.; Breukink, S.; van Koeveringe, G.
Abstract : Aims: (i) To describe and analyse pelvic floor dysfunction symptoms in women referred to a Pelvic Care Centre (PCC). (ii) To describe the triage process of the same patients based on response to a first‐contact interview. Methods: Triage started with a telephone interview using previously constructed questions, asking for seven types of PF complaints during the preceding 6 months. If present, complaint severity was registered on a 0–10 scale. Next, these first‐contact complaints were used to describe patient case mix profiles using cross‐tabular analysis. Later on, at first PCC visit, an intake questionnaire containing questions on specific PF health problem(s) was filled out. This procedure contributed to a firm baseline characterization of the individual patient profile and a clinically valid allocation to structured, predefined assessment, and treatment. Results: From 2005 to 2013, 4473 first‐time patients (mean age 56.9 (SD 16.2) have been referred to the PCC. Most frequently mentioned complaints: voiding dysfunction (59.5%), urinary incontinence (46.6%), prolapse (41.1%), fecal incontinence (15.1%), constipation (12.6%), and sexual problems (4.6%). A first appointment to a single specialist was determined in 3.110 (69.5%) patients, in 1.192 (26.7%) consultation of >1 specialist. Data analysis revealed higher‐order interactions between PF complaints, suggesting patient profile complexity and patient population heterogeneity. Conclusions: More than one out of four PCC patients showed multifactorial problems, needing >1 specialist. PF complaints either turned out to stand alone or cluster with others, or even to strengthen, weaken, nullify, or inverse relationships. Neurourol. Urodynam. 35:503–508, 2016 . © 2015 Wiley Periodicals, Inc.